Revisiting the Compensation Submission Framework for Terrorism Victims: An Analysis of Constitutional Court Decision No. 103/PUU-XXI/2023 - Wijanarko, Dimas; Romaida Hutabarat, Rugun (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
In the submission of compensation for victims of terrorism, there should be a legal framework that provides justice and comprehensive protection for victims without administrative barriers or time limitations for claim submissions. In reality, terrorism victims often face difficulties in accessing compensation due to convoluted procedures and legal uncertainties, particularly related to the time limit for submission. This research aims to analyze the legal framework for compensation submission for terrorism victims based on Constitutional Court Decision No. 103/PUU-XXI/2023 and the changes in compensation procedures following the decision. This article uses a library research method with a qualitative approach, analyzing legal documents and relevant literature to describe and explain the legal dynamics in compensation for terrorism victims. Constitutional Court Decision No. 103/PUU-XXI/2023 brings significant changes by removing the time limit for compensation submission, providing broader opportunities for victims. However, challenges in implementing this decision still exist, particularly regarding administrative barriers and the lack of awareness and information for victims.